THE EFFECTIVENESS OF KNOW –WANT-LEARN (KWL) STRATEGY IN TEACHING READING COMPREHENSION - Husnaini Husnaini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
The objectives of the research is to find out whether or not the use of KWL strategy is more effective than non KWL strategy in improving students’ interpretive comprehension. The research applied quasi experimental design in which the researcher used two groups namely experimental group with treatment by using KWL strategy and control group non KWL strategy. The subject of this research was the eighth grade students of SMP Neg. 9 Palopo with the number of sample is 60 students, 30 students in experimental group and 30 students in control group. The researcher gave pretest before treatment to both groups and gave treatment to experimental group in six meetings and the last the researcher gave posttest. The data were collected through reading comprehension test in objective test form. The research result indicated that the use of KWL strategy is more effective than non KWL strategy in improving students’ interpretive comprehension. It was proven by the t-test of students’ posttest on this level of comprehension between experimental and control group where Probability value was lower than alpha (.000<0.05). It indicates that null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted because P-value < α.